Residual Durability Performance of Glass Fiber Reinforced Concrete Damaged by Compressive Stress Loads - Yıldırım, Musa; Bilir Özhan, Hacer (Periodica Polytechnica Civil Engineering, 2023)
Concrete is exposed to a variety of stresses throughout its service life, which can result in cracks and damage. The use of fibers in concrete mixtures is known to improve the mechanical and durability properties of the concrete. In this study, glass fiber-reinforced concrete cube specimens were produced and stressed at 70 and 90 percent of their maximum compressive strength. The effects of stress loading-induced cracks and glass fiber reinforcements on mechanical and durability properties of concrete specimens were investigated using UPV, capillary water absorption, acid effect, and high-temperature effect tests. Glass fibers increased compressive strength and reduced water absorption in specimens that were not stressed. On the other hand, glass fibers increased the durability of stressed specimens at both degrees of compressive load stress. The bridging effects of glass fibers reduced crack creation, resulting in improved UPV test results. Glass fibers did not dissolve in acid solution due to their chemical resistance, resulting in less weight loss and higher compressive strength in concrete specimens. In the high-temperature effect tests, decreasing compressive strength values were observed as the stress load and temperature levels increased. However, such reductions were lower for glass fiber reinforced concrete than for control concrete without glass fiber. As a result of the present findings, glass fiber reinforcements prevent stress-induced cracks, making the concrete more durable and stronger against external forces.